1993
DOI: 10.1086/646783
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Immunization with a Combination of Serum and Recombinant Hepatitis B Vaccines

Abstract: A regimen that combines serum and recombinant hepatitis B vaccines may not produce as high an antibody level as three doses of the same vaccine. Those who began immunization with serum vaccine and concluded with recombinant vaccine should be monitored for an accelerated drop in serum antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There have been 2 studies evaluating the immunogenicity and the protective efficacy of combined vaccination. [101,102] The first concluded that the booster effect of RV was inferior to that of PDV in healthcare workers who had received 2 doses of PDV. It was also suggested that there might be an accelerated decline in anti-HBs when different vaccines were used in combination.…”
Section: Use Of Plasma-derived and Recombinant Vaccines In Combinationmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been 2 studies evaluating the immunogenicity and the protective efficacy of combined vaccination. [101,102] The first concluded that the booster effect of RV was inferior to that of PDV in healthcare workers who had received 2 doses of PDV. It was also suggested that there might be an accelerated decline in anti-HBs when different vaccines were used in combination.…”
Section: Use Of Plasma-derived and Recombinant Vaccines In Combinationmentioning
confidence: 99%
“…It was also suggested that there might be an accelerated decline in anti-HBs when different vaccines were used in combination. [101] Another study demonstrated that a combined vaccination with PDV and RV was both protective and immunogenic in infants. [102] The protective efficacy of combined vaccination in high-risk infants ranged from 89 to 93%, similar to that in other reports using either PDV or RV (table I).…”
Section: Use Of Plasma-derived and Recombinant Vaccines In Combinationmentioning
confidence: 99%
See 1 more Smart Citation